EFFECT OF PROFITABILITY AND ASSET STRUCTURE ON CAPITAL STRUCTURE (IN SHARIA BASED MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE IN 2016-2019 PERIOD) - Siti Mujiatun; Rahmayati Rahmayati; Dwita Ferina (Proceeding International Seminar of Islamic Studies, 2021)
The capital structure describes the company's permanent financing consisting of long-term debt and equity. Capital structure decisions are influenced by profitability and other variables. In this study, the authors tested the variables that affect the capital structure including profitability and asset structure. The type of data in this study was quantitative. The data analysis technique in this study uses multiple linear regression analysis equations. In this study, the dependent variable is capital structure and the independent variable is profitability and asset structure. The results indicate that profitability and asset structure have a positive and significant effect on capital structure of 9,542 with a significance value of 0,000 in sharia-based manufacturing companies listed on the Indonesian Stock Exchange for the period 2016 - 2019. Partially, the two independent variables have a significant effect on Structure Capital (DER) is 3.338 with a significance of 0.001 and a positive ? value of 0.321 together on Capital Structure and Asset Structure has a positive and significant effect on Capital Structure (DER) of 2.723 with a significance value of 0.008 and a positive ? value of 0.262 in Sharia-based manufacturing companies listed on the Indonesian Stock Exchange for the period 2016 - 2019.Keywords: Capital Structure, Profitability, Asset Structure.